Controlled release formulation of zinc hydroxide nitrate intercalated with sodium dodecylsulphate and bispyribac anions: a novel herbicide nanocomposite for paddy cultivation - Norhayati Hashim (Tanjong Malim, 2019)
Controlled release formulation of zinc hydroxide nitrate intercalated with sodium dodecylsulphate and bispyribac anions: a novel herbicide nanocomposite for paddy cultivation by Norhayati Hashim